2012
DOI: 10.1038/jid.2011.447
|View full text |Cite
|
Sign up to set email alerts
|

SERCA2-Controlled Ca2+-Dependent Keratinocyte Adhesion and Differentiation Is Mediated via the Sphingolipid Pathway: A Therapeutic Target for Darier's Disease

Abstract: Summary Darier’s Disease (DD), caused by mutations in the endoplasmic reticulum (ER) Ca2+ ATPase ATP2A2 (SERCA2b), is a skin disease that exhibits impaired epidermal cell-to-cell adhesion and altered differentiation. Although previous studies have shown that keratinocyte Ca2+ sequestration and fluxes are controlled by sphingolipid signaling, the role of this signaling pathway in DD previously has not been investigated. We show here that sphingosine levels increase and sphingosine kinase (SPHK1) expression decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 34 publications
8
47
0
Order By: Relevance
“…Recently, S1P has been shown to have signaling properties that regulate keratinocyte cell function (31)(32)(33)(34)(35)(36). Here, we report that the deletion of Sgpp1, the gene encoding SPP1, greatly disturbs epidermal homeostasis in mice.…”
Section: Sphingosine 1-phosphate (S1p)mentioning
confidence: 76%
See 2 more Smart Citations
“…Recently, S1P has been shown to have signaling properties that regulate keratinocyte cell function (31)(32)(33)(34)(35)(36). Here, we report that the deletion of Sgpp1, the gene encoding SPP1, greatly disturbs epidermal homeostasis in mice.…”
Section: Sphingosine 1-phosphate (S1p)mentioning
confidence: 76%
“…S1P has long been known to induce elevations of intracellular Ca 2ϩ levels through the release from internal stores (5, 6), and its metabolism is believed to serve as a complementary Ca 2ϩ signaling pathway to promote keratinocyte differentiation (31). Elevating S1P levels through sphingosine kinase activation or lowering S1P lyase levels has been shown to increase Ca 2ϩ levels and promote differentiation (33,34). Furthermore, the up-regulation of alkaline and acid ceramidases (see scheme in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2e). We further demonstrated that the mRNA expression level of SERCA2, which is responsible for Ca 2+ uptake in the keratinocytes (26,27), was significantly down-regulated, indicating that the amount of Ca 2+ in the endoplasmic reticulum may be reduced by FDP.…”
Section: Resultsmentioning
confidence: 79%
“…Impaired adhesion, a feature of the disease, is likely to result from changes in DSP traffi cking (Celli et al, 2012;Dhitavat et al, 2003;Hobbs et al, 2011). The desmosomal proteins DSP, DSG3 and DSC3 appeared disorganised with a thicker and punctuated distribution under the plasma membrane, while DSG3 and DSC3 also presented perinuclear staining, suggesting that they had been retained in the endoplasmic reticulum (ER).…”
Section: Darier ' S Diseasementioning
confidence: 99%